Development of nanocubosomes co-loaded with dual anticancer agents curcumin and temozolomide for effective colon cancer therapy - Almoshari, Yosif; Iqbal, Haroon; Razzaq, Anam; Ali Ahmad, Khalil; Khan, Muhammad Khalid; Saeed Alqahtani, Saad; Sultan, Muhammad H.; Ali Khan, Barkat (Drug delivery, 2022)
Current research aimed to develop nanocubosomes co-loaded with dual anticancer drugs curcumin and temozolomide for effective colon cancer therapy. Drugs co-loaded nanocubosomal dispersion was prepared by modified emulsification method using glyceryl monooleate (GMO), pluronic F127 and bovine serum albumin (BSA) as a lipid phase, surfactant, and stabilizer, respectively. The resulting nanocubosomes were characterized by measuring hydrodynamic particle size, particle size distribution (PSD), drug loading capacity (DL), encapsulation efficiency (EE), colloidal stability and drug release profile. We also physiochemically characterized the nanocubosomes by transmission electron microscopy (TEM), Fourier transform infrared (FTIR), and x-rays diffraction (XRD) for their morphology, polymer drug interaction and its nature, respectively. Further, the in-vitro cell-uptake, mechanism of cell-uptake, in-vitro anti-tumor efficacy and apoptosis level were evaluated using HCT-116 colon cancer cells. The prepared nanocubosomes exhibited a small hydrodynamic particle size (PS of 150 ± 10 nm in diameter) with nearly cubic shape and appropriate polydispersity index (PDI), enhanced drug loading capacity (LC of 6.82 ± 2.03% (Cur) and 9.65 ± 1.53% (TMZ), high entrapment efficiency (EE of 67.43 ± 2.16% (Cur) and 75.55 ± 3.25% (TMZ), pH-triggered drug release profile and higher colloidal stability in various physiological medium. Moreover, the nanocubosomes showed higher cellular uptake, in-vitro cytotoxicity and apoptosis compared to free drugs, curcumin and temozolomide, most likely because its small particle size. In addition, BSA-stabilized nanocubosomes were actively taken by aggressive colon cancer cells that over-expressed the albumin receptors and utilized BSA as nutrient source for their growth. In short, this study provides a new and simple strategy to improve the efficacy and simultaneously overawed the adaptive treatment tolerance in colon cancer.